Proceedings 2002 IEEE International Conference on Robotics and Automation (Cat. No.02CH37292)
DOI: 10.1109/robot.2002.1013423
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel vibrotactile display for teleoperated assembly

Abstract: This paper presents the design and testing of a multi-channel vibrotactile display. It is composed of a cylindrical handle with four embedded vibrating elements driven by piezoelectric beams. Vibrations are transmitted to the hands through arrays of pins. The device was tested in sensory substitution for conveying force information during a teleoperated peg insertion. Results show that the device is effective in reducing peak forces during the insertion task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…-Dynamic physical processes, such as rolling (Yao and Hayward, 2006) or breaking. -Force magnitude and/or direction, specifically arising from contact forces (Massimino, 1991;Debus et al, 2001Debus et al, , 2002.…”
Section: Vibrotactile (Vt) Feedback In Teleoperation or Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…-Dynamic physical processes, such as rolling (Yao and Hayward, 2006) or breaking. -Force magnitude and/or direction, specifically arising from contact forces (Massimino, 1991;Debus et al, 2001Debus et al, , 2002.…”
Section: Vibrotactile (Vt) Feedback In Teleoperation or Vrmentioning
confidence: 99%
“…Example. VT augmentation of a haptic manipulandum (Debus et al, 2002) Debus and his colleagues studied VT enhancement of a PHANTOM haptic interface for the display of forces at the peg-like end effector of a slave robot ( Debus Fig. 11.…”
Section: Vibrotactile (Vt) Feedback In Teleoperation or Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…A study investigating the effect of sensory substitution for a peg-inhole insertion task has shown that both visual feedback and vibrotactile feedback of haptic information can reduce peak forces, as compared with the case in which no feedback of haptic information is provided to the users [6]. Moreover, findings have shown that visual sensory substitution improves a userÕs sensitivity for detecting small forces by allowing the use of high feedback gains without a slowing of hand movements [19].…”
Section: Benefitsmentioning
confidence: 99%
“…While force feedback remains a more intuitive means of relaying haptic information to the user, visual sensory substitution for force feedback (or "visual force feedback") may be able to provide sufficient feedback of an instrument's contact with tissue under certain conditions. Study of the effect of sensory substitution for a peg-inhole insertion task has shown that both visual feedback and vibro-tactile feedback of haptic information can reduce the peak forces compared to the case where no feedback of haptic information is provided to the users [10]. For the suturing task, quantifying the difference in the user's performance between manual operation and robotic teleoperation in presence of auditory/visual sensory substitution has been the subject of another study [11].…”
Section: Sensory Substitution For Haptic Feedbackmentioning
confidence: 99%